A Rare Presentation of Myeloid Sarcoma as Supraclavicular Mass: A Case Report in Chronic Myeloid Leukemia - Khan, Amna; Faizan, Umar; Hassan Ramzi, Syed Ibraheem ul; Javid, Ans; Abbas, Husnain; Ali, Huzafa; Pandeya, Ajay; Maharjan, Prerana (Journal of Nobel Medical College, 2025)
Myeloblasts or immature myeloid cells form myeloid sarcoma, an extramedullary myeloid tumor which commonly affects sites like skin, soft tissues, bone, peritoneum, and lymph nodes. Myeloid sarcoma typically occurs during accelerated and blast phase of chronic myelogenous leukemia. It is a very uncommon presentation of CML in its early medullary chronic phase. This is a rare case of CML that presented with an ulcerative lesion on the left clavicular area and a soft swelling in the anterior cervical region above the clavicle, which are aggressive and rare extramedullary manifestations of chronic myeloid leukemia. Notable finding include TLC of 418.92 X 10E9/L, peripheral blood film showed anisocytosis, poikilocytosis, polychromasia, macrocytosis and nucleated RBC, karyotyping for Philadelphia Chromosome was positive. Overall findings are consistent with myeloproliferative neoplasm (chronic myeloid leukemia in chronic phase). The patient started on TKI therapy and showed improvement initially. Despite improvement, patient’s relapse suggests potential resistance, emphasizing the need for vigilant follow-up and consideration of alternative treatment strategies.